A Comparative Study Of the Students’ Competence in Finding Figurative And Lexical Meaning To Improve Speaking Ability at the Eleventh Grade of SMAN 1 Maja - Titin Kustini (Journal of English Language Learning, 2024)
Students often have difficulty understanding figurative meanings compared to lexical meanings. Figurative meaning refers to the immediate meaning conveyed when a language is spoken in isolation, while the secondary meaning is dependent on the context; this is known as figurative meaning. On the other hand, lexical meaning refers to the literal meaning of language elements as symbols of things. The research aims to assess students’ proficiency in identifying figurative and lexical meanings and to compare this between the experiment and control classes. The study involved 46 students from the eleventh year at SMAN 1 Maja. It was a quantitative research study, indicating that the data collected were presented in numerical form and then interpreted using statistical analysis. The research tools included a questionnaire, observation, pre-test, and post-test. The results of the research showed that students' competence in identifying figurative and lexical meanings was low during the pre-test (5.23) and reached a sufficient level during the post-test (6.07). The post-test scores for figurative and lexical meanings were 6.57 and 6.92, respectively. The difference between pre-test and post-test scores was analyzed using t-tests, which yielded significant results for both the control class (t=4.84) and the experiment class (t=3.94) for figurative meaning, and for lexical meaning in the control class (t=2.712) and the experiment class (t=3.98). These results demonstrate that students' competence in identifying figurative and lexical meanings can improve their English proficiency, particularly in enhancing their speaking ability.